PENGEMBANGAN RUANG ENCLOSURE JALAN DI KAWASAN KOMERSIAL, BANDAR JAYA, LAMPUNG TENGAH - Panji Kurniawan (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2011)
When thinking of a city, the easiest thing that can be recorded from that city is the activity in its streets in which the city’s all activities can be reflected in its external performance through public open space which in this case is a street. In fact, the lively condition of a city can be measured from its streets that form the structure of the city. Proklamator Raya, Bandar Jaya, is a street that forms the city structure of Bandar Jaya. This street is not only as a primary artery street of the citybut also in a wider scale as transportation line of trans-Sumatera. Therefore, this street has high complexity seen from vehicle intensity, activity and other interest. Commerciality is one activity that dominates this area. As a generator, a street becomes the easiest access for economic sectors that become a logic consequence. Unfortunately, the development is imbalance with its existence in a wider context. The spreading of commerciality concentrated along a street, the decreasedattention upon green areas, and the heaps of signage without urban planning development are the influential problems for the quality of the area. The elements should thus be present with a good composition in order to enhance the taste toward the space of Proklamator Raya Street. Referring to the taste of the space, this is inseparable with the elements of the forming of street walls and street space that leads to the enclosure of the space. Therefore, this study aims at (1) analyzingelements that form enclosure in Proklamator Raya Street; (2) analyzing the quality of enclosure; and (3) giving direction of enclosure of street space that fits Proklamator Raya Street as a commercial area in Bandar Jaya. The research paradigm used in this study was rationalistic qualitative, emphasizing on the understanding about problems in the field based on real condition. Analysis was done with dialoging the element data of the forming of street wall (2 vertical dimensions) and street space dimension (2 horizontal dimensions) that finally form street section with different scales. The data were then dialoged with theory of ideal enclosure. The results of this study showed that there were two factors that affected the quality of an enclosure of road space were (1) direct influential factors comprising (a) setback and elements’ height (b) fixedelements’ type, pattern, height and layout (c) moving elements that form street wall and (2) indirect influential factors comprising (a) the present of land use and (b) circulation pattern in the area Keywords: Street, Enclosure, Street Wall and Street Space.